Interventional Algorithms for the Control of Coagulopathic Bleeding in Surgical, Trauma, and Postpartum Settings: Recommendations From the Share Network Group. (March 2016) - Carvalho, Manuela; Rodrigues, Anabela; Gomes, Manuela; Carrilho, Alexandre; Nunes, António Robalo; Orfão, Rosário; Alves, Ângela; Aguiar, José; Campos, Manuel
Several clinical settings are associated with specific coagulopathies that predispose to uncontrolled bleeding. With the growing concern about the need for optimizing transfusion practices and improving treatment of the bleeding patient, a group of 9 Portuguese specialists (Share Network Group) was created to discuss and develop algorithms for the clinical evaluation and control of coagulopathic bleeding in the following perioperative clinical settings: surgery, trauma, and postpartum hemorrhage. The 3 algorithms developed by the group were presented at the VIII National Congress of the Associação Portuguesa de Imuno-hemoterapia in October 2013. They aim to provide a structured approach for clinicians to rapidly diagnose the status of coagulopathy in order to achieve an earlier and more effective bleeding control, reduce transfusion requirements, and improve patient outcomes. The group highlights the importance of communication between different specialties involved in the care of bleeding patients in order to achieve better results.